2013
DOI: 10.7773/cm.v39i1.2165
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of aluminosilicate-based products for detoxification of aflatoxin-contaminated diets for juvenile Pacific white shrimp, Litopenaeus vannamei

Abstract: The safety and effectiveness of four aluminosilicate-based products (Novasil Plus, Zeolex Extra, Mycofix Select, and Fixat) were tested for 42 days on juvenile Pacific white shrimp, Litopenaeus vannamei, fed diets containing corn grains that had been previously inoculated with Aspergillus parasiticus and then sterilized. Two control diets, one uncontaminated and another contaminated with the contaminated corn grain, were elaborated to contain a final concentration of 0 and 75 μg kg–1 total aflatoxins. Both die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…Among the strategies for reduction in AF exposure in the feed industry, the use of mineral and organic adsorbents has been reported in vivo e in vitro (Marroquin-Cardona et al, 2009). For aquatic organism, it has been observed that the addition of different type of clays to AF diet can greatly reduce the harmful effect that this mycotoxin produces on the performance parameters, and this has been demonstrated in studies conducted with L. vannamei (García-Pérez et al, 2013) and P. monodon (Arunlertaree et al, 2007). However, those strategies are intended to reduce the exposure before the AF can be absorbed in the gastrointestinal tract and offer little or no protection once the AF is absorbed to the blood and its oxidative damage to tissues is exerted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the strategies for reduction in AF exposure in the feed industry, the use of mineral and organic adsorbents has been reported in vivo e in vitro (Marroquin-Cardona et al, 2009). For aquatic organism, it has been observed that the addition of different type of clays to AF diet can greatly reduce the harmful effect that this mycotoxin produces on the performance parameters, and this has been demonstrated in studies conducted with L. vannamei (García-Pérez et al, 2013) and P. monodon (Arunlertaree et al, 2007). However, those strategies are intended to reduce the exposure before the AF can be absorbed in the gastrointestinal tract and offer little or no protection once the AF is absorbed to the blood and its oxidative damage to tissues is exerted.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rate, feed consumption, feed conversion rate and survival rate were calculated by using formulas described by García-Pérez et al (2013). Before recording weight, excess water in shrimp was removed by blotting with absorbent cotton fabric.…”
Section: Growth Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Las dietas se elaboraron de acuerdo con la metodología descrita por García-Pérez et al (2013). Los ingredientes fueron mezclados en una mezcladora KitchenAid durante 10 min y, luego de agregar agua tibia (30%), durante 15 min.…”
Section: Elaboración De Dietas Experimentalesunclassified
“…The diets were elaborated following the method described by García-Pérez et al (2013). The ingredients were mixed in a KitchenAid mixer for 10 min and for another 15 min after warm water (30%) was added.…”
Section: Elaboration Of the Experimental Dietsmentioning
confidence: 99%